Empire of cotton: a new history of global capitalism - Beckert, Sven (New York, 2014)
"For about 900 years, from 1000 to 1900, cotton was the world's most important manufacturing industry. It remains a vast business - if all the cotton bales produced in 2013 had been stacked on top of each other they would have made a somewhat unstable tower 40,000 miles high. Sven Beckert's superb new book is a history of the overwhelming role played by cotton in dictating the shape of our world. It is both a gripping narrative and a brilliant case history of how the world works."